Chronic non-communicable diseases: cardiovascular risk factors in university professors - Ivaneusa Mira Santos; Daniela de Souza Pinto; Jerusa da Mota Santana; Leila Graziele de Almeida Brito; Karla Rocha Pithon (O Mundo da Saúde, 2018)
Chronic non-communicable diseases are multifactorial pathologies that begin in any life cycle and are prolonged, most often associated with cardiovascular risk factors. The aim of the present study was to identify the association of chronic non-communicable diseases with cardiovascular risk factors in college professors. 190 college professors participated in the study; an online questionnaire was developed with socio-demographic information, professional activity, life habits, information regarding the heredity of cardiovascular diseases, presence of chronic non-communicable diseases and stress level. A descriptive analysis was performed (mean, standard deviation and proportion) and Fisher's exact test was used for chronic non-communicable disease associations. The participants’ mean age was 40.96±8.70 years and 61.1% were female. Systemic arterial hypertension was associated with heredity (p=0.052), overweight (p=0.005), and marital status (p=0.036). Age over 40 years (p=0.036), males (p<0.001) and frequency of physical exercise (p=0.029) were associated with obesity. There was an association between the presence of diabetes mellitus and life habits (p=0.005), marital status (p=0.026) and obesity (p=0.052). It was verified that chronic non-communicable diseases were associated with cardiovascular risk factors in university professors, with an emphasis on their body mass index, age, sex and heredity.